(untitled) (Health Renaissance, 2014)
Along with clinical training, encouraging practice of Evidence Based Medicine (EBM) plays a crucial role in training tomorrow’s doctors. Involvement of medical students in research activities is crucial in developing critical thinking, efficient literature-searching, and application of formal rules of evidence in evaluating the clinical literature, and publishing research to contribute to medicine. Though significant progress has been made in the recent years, the concept of student research is relatively new and less implemented in Nepal. Mandatory research in the medical curriculum, electives or dual degree programs can not only promote student research but also enhance better EBM practices among medical professionals. DOI: http://dx.doi.org/10.3126/hren.v11i3.9660 Health Renaissance 2013;11(3):297-300